(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the twenties and early thirties of twentieth centuryGandhi was not the undisputed leader of the masses. There were many who did nothave faith in his non-violent non-cooperation movement. But his social reformslike eradication of untouchability and picketing toddy shops and sarvodayaideals received the attention of one and all. The humiliated and long neglectedsection of the society at last found one who championed their cause. Thisarticle explains how Mahatma Gandhiis introduced into the Indian English fiction in various ways.